Preserved or slightly depressed ejection fraction and outcomes after myocardial infarction. Issue 1028 (25th March 2011) - Badheka, Apurva O; Rathod, Ankit; Bharadwaj, Aditya S; Manickam, Palaniappan; Kizilbash, Mohammad A; Veeranna, Vikas; Jacob, Sony; Afonso, Luis
Abstract : Background: Left ventricular ejection fraction (EF) in post-myocardial infarction (MI) patients is a strong predictor of adverse cardiovascular events. Although resting EF as measured by transthoracic echocardiography (TTE), contrast ventriculography (CNV), and radionuclide angiography (RNA) exhibit high correlation, there is only modest agreement between these modalities. This study sought to explore whether modality of EF assessment influences prognostication of post-MI patients with normal or slightly reduced EF. Methods and results: The National Heart, Lung, and Blood Institute (NHLBI) limited access dataset of the Prevention of Events with Angiotensin Converting Enzyme Inhibition (PEACE) Trial (1996–2003, n=8290) comparing trandolapril versus placebo was used. The cohort was partitioned into TTE (n=2582), RNA (n=816), and CNV (n=1155) groups based on modality of EF assessment. EF was a significant predictor of cardiovascular mortality (HR 0.97, 95% CI 0.95 to 0.98; p<0.005) and all cause mortality (HR 0.98, 95% CI 0.97 to 0.99; p=0.0002) on multivariate analysis in this population with preserved or mildly depressed EF. Although CNV, TTE, and RNA groups differed significantly in terms of baseline variables, no appreciable differences were noted between RNA (HR 1.13, 95% CI 0.85 to 1.50; ns) and CNV (HR 1.13, 95% CI 0.99 to 1.27; ns) groups, compared with TTE for all cause mortality. Similarly, no significant differences were observed for cardiovascular mortality between RNA (HR 1.23, 95% CI 0.82 to 1.84; p=0.31) and CNV (HR 1.14, 95% CI 0.78 to 1.67, p=0.49) versus TTE. Conclusion: EF is a significant predictor of all-cause mortality and cardiovascular mortality in patients with preserved or mildly depressed EF. Modalities of EF measurement are interchangeable and do not play a significant role in prognostication in a post-MI population.